Speed isn't everything: A multi-criteria analysis of the broadband consumer experience in the UK. (February 2018) - Stocker, Volker; Whalley, Jason
Abstract: In this paper, we demonstrate that there is more to consumer experience than just broadband access speed. We identify and describe a complex and dynamic set of interactions that occur between different factors that collectively determine consumer experience. We suggest that the relationship between broadband speed and consumer experience follows an inverted U-shape. Access speed is necessary to provide consumers with a good experience, but it is not sufficient. Based on our findings, a more nuanced understanding of the market for broadband Internet access products is outlined and a foundation for deriving valuable policy implications is developed. Highlights: Broadband speed is a necessary but not sufficient component of consumer experience. Consumer experience is shaped by complex interactions across the value chain. The relationship between network performance, QoS and QoE is explored. Relationship between speed and consumer experience follows an inverted U-shape.